Using Climate Simulators to Facilitate Peacebuilding: A Study of Practice - Johnson, Ciara Renee (In Factis Pax: Journal of Peace Education and Social Justice, 2025)
As the climate crisis approaches a critical juncture, the pursuit of ecological peace becomes increasingly vital to conflict resolution and peacebuilding efforts. This article explores the pivotal role of climate simulators in fostering peacebuilding through informed, data-driven dialogues. These tools anchor peacebuilding initiatives in scientific reality, enabling the identification and assessment of the co-benefits and co-considerations associated with climate-related actions. Furthermore, they promote scenario-based planning within peacebuilding contexts. Drawing from the author's personal experiences with the En-ROADS Climate Simulator in both secondary education and peacebuilding education settings, this article demonstrates the practical application of these tools. The En-ROADS Climate Simulator serves as a powerful example of how climate simulators can be integrated into educational frameworks to enhance understanding and engagement. The article provides actionable recommendations for incorporating climate simulators into broader educational environments, community advocacy efforts, and legislative processes. By emphasizing the significance of data visualizations tailored to specific geographic locations, the article highlights how personalized climate simulation tools can inform and support sustainable, long-term peacebuilding strategies. Ultimately, this article underscores the transformative potential of climate simulators in bridging the gap between scientific data and peacebuilding practices, advocating for their active adoption to address the multifaceted challenges posed by the climate crisis.